Disruption Disrupted through the Meta-Analysis - Ernest Vlačić (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
Innovation, particularly when realized through structured innovation process strategically contributes to firms' mission to achieve and maintaining a long-term and sustainable competitive advantage. Recently, over half of the Fortune 500 companies have disappeared since 2000 by being merged, acquired, or gone bankrupt. Many of them because they did not properly react on uncertain and dynamic global market dynamisms where the innovative strategic positioning present on of the most driving critical success factor. This is notable particularly when it comes to the field of disruptive innovations which presents one of the challenging phenomenon that corporations have to face to. Due to its nature and genesis the emergence of disruptive innovation tents to slip under the radars of incumbents and causing plausible or sometimes significant damages by disrupting their comfortable market positioning. Therefore, a deeper understanding and the comprehensive overview of the existing knowledge base related to the theory of disruptive innovations in influencing corporate business practices lies in the focus of this research. Based on a Web of Science Core Collection base, this paper presents a bibliometric analysis of relevant publications on disruptive innovation with the specific aim of gaining a deeper insight into the relevance of the impact of such innovation in context of corporate business. In terms of methodology, by conducting exploratory secondary research the available bibliographic data related to the field of disruptive innovation studies have been analyzed in detail. As the instrument for determining the relevance and influence of the impact of disruptive innovation, a meta-analysis of published papers was performed. It is hoped that the results obtained will contribute to a better understanding of disruptive innovation and its areas of influence, as well as guide and focus potential future research efforts particularly in the economies where it wasn't evaluated sufficiently.
Keywords: 650; Disruptive innovation; Corporations; Meta-analysis; Strategic positioning